Gambaran Persepsi dan Sikap Anak Usia Sekolah Dasar Tentang Kesehatan Seksual dan Pencegahan Kekerasan Seksual di Bantul, Yogyakarta - Retno Sumiyarrini; Latifah Susilowati; Dwi Yati (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2022)
Background: Child Sexual Abuse was a major global problem widespread in many cities in Indonesia. Komisi Perlindungan Anak Indonesia or Indonesian Children Protection Commission (KPAI) records as many as 1.880 children become victims of sexual abuse activities such as rape, fornication, sodomy and pedophilia. Around 62% of victims experienced this abuse during their elementary school period. However, little is known about the perception and attitude of school children toward this issue in Yogyakarta. Purpose: The aim of this research is to investigate the perception and attitude of school-age children toward sexual health and child sexual abuse prevention program. Method: This was a cross-sectional study and was conducted between June-October 2021 in one elementary school in Bantul, Yogyakarta. The participant of this study was 90 elementary school children aged 6-12 years, which recruited using multistage random sampling. The outcome was measured using a questionnaire and was analyzed. Result : Majority of respondent (84,4%) has positive perception and attitude toward sexual health and child abuse. Most of respondent also has positive perception and attitude on item maintenance the hygiene of reproductive organ (63,3%), preventing sexual abuse by protecting the body from intimate groping (75,6%), refusing stranger approach (66,7%), physical against towards abuse (77,8%), and reporting when sexual abuse exist (82,2%). Conclusion: Respondent has positive perception and attitude toward sexual abuse as implication of good comprehension about sexual abuse